2008
DOI: 10.1007/s00464-008-9764-8
|View full text |Cite
|
Sign up to set email alerts
|

Timing of cholecystectomy after endoscopic sphincterotomy for common bile duct stones

Abstract: Background According to the literature, the conversion rate for laparoscopic cholecystectomy (LC) after endoscopic sphincterotomy (ES) for cholecystodocholithiasis reaches 20%, at least when LC is performed 6 to 8 weeks afterward. It is hypothesized that early planned LC after ES prevents recurrent biliary complications and reduces operative morbidity and hospital stay. Methods All consecutive patients who underwent LC after ES between 2001 and 2004 were retrospectively evaluated. Recurrent biliary complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 27 publications
3
73
0
5
Order By: Relevance
“…If disease progression is the main reason for higher conversion rates in subsequent LC, then longer intervals would be expected to be associated with higher conversion rates. However, of the studies that have specifically investigated time intervals between the two procedures [6,8,9], one study found a shorter interval to be associated with fewer conversions to open cholecystectomy [8], while the other studies found no association. We also found that post-ERCP time interval and conversion rates were not associated with each other.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…If disease progression is the main reason for higher conversion rates in subsequent LC, then longer intervals would be expected to be associated with higher conversion rates. However, of the studies that have specifically investigated time intervals between the two procedures [6,8,9], one study found a shorter interval to be associated with fewer conversions to open cholecystectomy [8], while the other studies found no association. We also found that post-ERCP time interval and conversion rates were not associated with each other.…”
Section: Discussionmentioning
confidence: 97%
“…The time interval between ERCP and LC has been investigated in retrospective studies [6,8,9], with one study finding that a shorter interval (<2 weeks) was associated with significantly fewer conversion to open cholecystectomy [8]. The aim of the present study was to investigate prospectively, in patients undergoing ERCP with sphincterotomy followed by LC, whether the time interval between the two procedures can affect the course of LC in terms of conversion rate or complications.…”
Section: Introductionmentioning
confidence: 96%
“…These recurrent complications were associated with a significantly longer hospital stay. Cholecystectomy within 1 week after ES, as followed in this study, may prevent recurrent biliary complications in the majority of cases and reduce the postoperative hospital stay [44].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Concomitantly, recurrent biliary complications in the majority of cases could be prevented minimised the postoperative hospital stay. 7 Earlier laparoscopic cholecystectomy was reported to improve outcomes after endoscopic sphincterotomy for choledochocystolithiasis. [8][9][10] It is cost effective in developing countries.…”
Section: Discussionmentioning
confidence: 99%